New method for the failure probability of strict circular consecutive-k-out-of-n:F system - Higashiyama, Y.; Rumchev, Ventsi (International Institute of Informatics and Cybernetics, 2010)
A recursive formula is given for calculating the failure probability for circular consecutive– k-out–of– n :F systems such that isolated strings of failures of length less than (which do not cause system failure) do not occur, or are immediately corrected; ie, when system failure occurs it is because all failures present are in strings of length at least. New method gives the failure probability function of circular strict system with time complexity O(nk 2).